Legal Aspects Of Flat Ownership In Indonesia - Muhammad Furqon; Muhammad Habib (International Asia Of Law and Money Laundering (IAML), 2022)
Technologically, the system of multi-storey buildings whose spaces can be used individually has long been known in Indonesia. The building ownership system is a single ownership system that is now developed is the ownership of multi-storey buildings with common property, called Flats, condominiums, or strata title. Hak Milik Satuan Rumah Susunan (HMSRS) is a new institution of material rights, this HMSRS is individual and separate, in addition to ownership of the unit of flats the ownership of the unit of flats (HMSRS) in question includes also joint ownership of the so-called shared parts, shared objects, and shared land where everything is an inseparable unity with the SRS concerned.